Ecological Requirement, Ethnopharmacology, Phytochemical and Antioxidant Capacity of Vaccinium arctostaphylos L. in Gilan Province (North of Iran) - Azad Khalili Musavi; Masoumeh Mazandarani; Suzan Rahimian; Mohammad Ghafourian (Journal of Medicinal Plants and By-products, 2016)
This study is investigate to ecological characters, ethnopharmacology, total phenols (TP), flavonoids (TF), anthocyanins (TA) contentand antioxidant capacity in leaves and fruit of Vaccinium arctostaphylos L. from two natural habitats from Gilan provinve, which has been used as a heart tonic ,anti diabeteand anti tumor. Ecological requirements were obtained in many field observation, ethno pharmacological survey was carried out among the well known indigenous herbal practitioners (60-78 ages) in South west of Gilan. The leaves and fruits of Vaccinium arctostaphylos L. were collected from two natural habitats (Khotbe sara,1600 m and Asalem, 1300 m) during Sep to Oct 2013, respectively. Methanol extracts were obtained by maceration, TP, TF and TA were determined by spectro photometrically, antioxidant capacity were measured  by total antioxidant capacity (TAC), reducing power (RP) and 2,2-Diphenyl-1-picrylhydrazyl (DPPH) in compare of BHT and BHA antioxidant standard and Quersetin content was messured by HPLC method. Results were showed that Vaccinium arctostaphylos L. is usually wild grow in silty loam soils (1300-1600m) and its fruit was appeared from June to September  .In both regions  phenolic components  had significant variation, ranging from TP content(263.17-471.26 mg GAEg-1),TF(186.18-289.17 mg QUE g-1) , TA  (74.3- 145.29 mg CydEg-1 ) and quersetin content (136.13-218.2 ppm respectively in 1300-1600m. Generally the fruits extract especially in 1600m had more source of phenolic componds, so was showed better antioxidant capacity (IC50 value 2.98±0.51 µg/ml) to will be confirmed the traditional uses of plant in these regions as an  good anti-inflammatory and anti diabetic.